Risky Development: Increasing Exposure to Natural Hazards in the United States - Iglesias, Virginia; Braswell, Anna E.; Rossi, Matthew W.; Joseph, Maxwell B.; McShane, Caitlin; Cattau, Megan; Koontz, Michael J.; McGlinchy, Joe; Nagy, R. Chelsea; Balch, Jennifer; Leyk, Stefan; Travis, William R. (Earth's future, 2021)
Losses from natural hazards are escalating dramatically, with more properties and critical infrastructure affected each year. Although the magnitude, intensity, and/or frequency of certain hazards has increased, development contributes to this unsustainable trend, as disasters emerge when natural disturbances meet vulnerable assets and populations. To diagnose development patterns leading to increased exposure in the conterminous United States (CONUS), we identified earthquake, flood, hurricane, tornado, and wildfire hazard hotspots, and overlaid them with land use information from the Historical Settlement Data Compilation data set. Our results show that 57% of structures (homes, schools, hospitals, office buildings, etc.) are located in hazard hotspots, which represent only a third of CONUS area, and ∼1.5 million buildings lie in hotspots for two or more hazards. These critical levels of exposure are the legacy of decades of sustained growth and point to our inability, lack of knowledge, or unwillingness to limit development in hazardous zones. Development in these areas is still growing more rapidly than the baseline rates for the nation, portending larger future losses even if the effects of climate change are not considered. Key Points More than half of the structures in the conterminous United States are exposed to potentially devastating natural hazards Growth rates in hazard hotspots exceed the national trend Risk assessments can be improved by considering multiple hazards, mitigation history and fine‐scale data on the built environment